Labor standards and economic integration in the European Union : an empirical analysis - Vivek H. Dehejia; Yiagadeesen Samy (Center for Economic Studies and ifo Institute (CESifo), 2006)
This study is motivated by frequent calls to harmonize labor standards across countries, which result from the fear that economic integration (and the accompanying liberalization of trade flows) will lead to an erosion of working conditions, as countries deliberately try to reduce labor standards in order to maintain competitiveness. We examine the linkages between labor standards and economic integration in the European Union (EU) and, in particular, investigate the following questions. First, whether the conventional wisdom that labor standards are important determinants of trade performance holds, and second whether there has been a race to the bottom of standards across countries with deeper integration. We follow a neoclassical factor-proportions framework to conduct our empirical investigation, and unlike previous studies, which rely mostly on cross-sectional data, we use a fully-fledged panel data set to explore the relationship between labor standards and export performance. Our estimates based on data for the period 1980-2001 for EU-15 countries provides mixed evidence regarding the conventional wisdom, and we find that trade performance is largely based on factor endowments. We also find mixed evidence for ó-convergence in labor standards.
Keywords: J8; 330